UGUCA: A spectral-boundary-integral method for modeling fracture and friction - Kammer, David S.; Albertini, Gabriele; Ke, Chun Yu (SoftwareX, 2021)
Uguca is a C++ parallel implementation of the spectral-boundary-integral method to model the dynamic failure of interfaces between two elastic half-spaces. Due to its computational efficiency, uguca is suitable for fundamental research on dynamic fracture mechanics, decohesion of composite interfaces, and the onset of frictional sliding. Therefore, its potential applications range from engineering sciences to earthquake mechanics modeling. The code architecture of uguca enables straight-forward implementation of additional constitutive interface laws, which provides the user with the option of tailoring the interface mechanics to the physics of their interest.